Estimativas de parâmetros genéticos e seleção de genótipos segregantes de soja - Rabelo, Paula Guimarães (2019)
The genetic improvement of soybean seeks the selection of genotypes with aspects of high standard that result in high productivity. For this to occur, the selection aims at achieving lineages with characteristics of productivity, resistance and adaptability. With the purpose to develop more productive cultivars, it is plausible the knowledge of the combination between the agronomic characters and the index analysis aiming at obtaining better prediction of gains and high efficiency in the selective process. Thus, the objective of the present study was to develop soybean progenies and to evaluate genetic parameters for the selection of superior genotypes that demonstrate a shorter total cycle and high grain yield. This study was developed at the Experimental Farm Capim Branco, belonging to the Federal University of Uberlândia, located in the city of Uberlândia - MG. First, an F2 segregating population was evaluated in the field from April to July 2018. In the first experiment of the F2 population (TMG 801x EMGOPA 316) seeds were arranged in the field and the genetic parameters of the characters and the genetic gains obtained by the indirect selection were evaluated. Characteristics such as APM and NNP in the F2 population presented estimates of heritability with values higher than 50% in the characters, suggesting favorable genotypes for selection. Grain production, the main character for selection gain estimates, of the F2 population reached a positive value of 46.31% in the selection gain, demonstrating a favorable selection of superior genotypes. In the second experiment, a segregating F3 and backcross population was fielded from October 2018 to March 2019. Sixty progenies and the parents TMG 801 and EMGOPA 316 were evaluated. Three plants were randomly selected of each line to be submitted to the phenotypic evaluations with the intention to select those that have superior genotypes. The heritability for soybean production from the TMG 801 and Emgopa 316 parents was 81.32%, favoring high selection gain estimates. The use of the selection indices of Mulamba and Mock (1978) and the distance of ideotype, considering the vegetative cycle, total and grain production, similarly identified the segregating soybean progenies. The progenies UFUS801X316-370, UFUS801X316-437 and UFUS801X316-RC2-5 stand out for their higher grain yield and semiprecoce cycle and are recommended for generations to come and new performance evaluations.